Frequency of Hematological Malignancies Based on Bone-Marrow Aspiration and Trephine Biopsy in Patients Presenting to Tertiary Care Hospital - Komal Iqbal, Zarmina Hussain, Saira Nasr Malik, Ansa Kalsoom Rahman, Mashal Riaz, Hameeda Qureshi, Mohtasim Billah, Assad Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hematological disorders are found commonly in the general population existing on both ends of the spectrum with minute disorders like iron deficiency anemia to as severe as bone marrow infiltration Objective: To assess the frequency of hematological malignancies based on bone-marrow aspiration and trephine biopsy in patients presenting to tertiary care hospital Methodology: The current study was cross-section descriptive study carried out at the Pathology department of Bacha Khan Medical College, Mardan from April 2013 to October 2021. Bone-marrow aspiration and trephine biopsy was done for all the patients. Data regarding gender, age, clinical examination and diagnosis was recorded on a proforma designed for this research. Results were analyzed by using IBM SPSS (version 23). Results: In our study, a total of 182 patients were included. The mean age (±SD) in the current study was 41 (12.6) years. Based on the malignant hematological disorder, acute myelogenous leukemia was diagnosed in 15 (23.08%) patients, acute lymphoblastic leukemia in (23.08%) patients, chronic myeloid leukemia in 14 (21.54%) patients, acute leukemias in 3 (4.62%) patients, Myeloproliferative neoplasms in 6 (9.23%) patients, Lymphoproliferative disease in 11 (16.92%) patients while plasma cell myeloma was diagnosed in 1 (1.54%) patients. Conclusion: Our study concludes that acute myelogenous leukemia (AML) and acute lymphoblastic leukemia (ALL) is the most common hematological malignancies in Bacha Khan Medical College followed by chronic myeloid leukemia (CML) which is the second highest malignancies in Bacha Khan Medical College in this specific time. Keywords: hematological malignancies, bone-marrow aspiration, trephine biopsy